1991
DOI: 10.1002/rcm.1290050303
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐induced conformational changes of polypeptides probed by electrospray‐ionization mass spectrometry

Abstract: Electrospray-ionization (ESI) mass spectrometry is used to monitor higher order structural changes of polypeptides induced by alteration of the pH or organic solvent composition in the protein solution environment. A bimodal charge-state distribution is observed in the ESI mass spectrum of ubiquitin (relative molecular mass 8565) in solutions containing small amounts (less than 20%) of organic solvents. The distribution of peaks at high m/z (low-charge state) is found to represent the protein in its native, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
250
2
3

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(269 citation statements)
references
References 22 publications
14
250
2
3
Order By: Relevance
“…ESI-MS conditions can be mild enough that proteins retain their native conformations and enzyme-substrate complexes or subunit interactions can be observed (Ganem et al, 1991a(Ganem et al, , 1991bKatta & Chait, 1991b;Baca & Kent, 1992;Ganguly et al, 1992;Drummond et al, 1993;Goodlett et al, 1993;Light-Wahl et al, 1993aLoo et al, 1993aLoo et al, , 1993bOgorzalek Loo et al, 1993). A number of investigators have taken advantage of the dramatic increase in charge state observed when some proteins are denatured to probe protein structure (Katta & Chait, 1991aLeBlanc et al, 1991;Loo et al, 1991Loo et al, , 1993b Mirzaet al, 1993). The applicability of mass spectrometry to biological problems would be greatly enhanced and expanded if methodologies were developed to analyze surfactant-containing protein solutions.…”
Section: Introductionmentioning
confidence: 99%
“…ESI-MS conditions can be mild enough that proteins retain their native conformations and enzyme-substrate complexes or subunit interactions can be observed (Ganem et al, 1991a(Ganem et al, , 1991bKatta & Chait, 1991b;Baca & Kent, 1992;Ganguly et al, 1992;Drummond et al, 1993;Goodlett et al, 1993;Light-Wahl et al, 1993aLoo et al, 1993aLoo et al, , 1993bOgorzalek Loo et al, 1993). A number of investigators have taken advantage of the dramatic increase in charge state observed when some proteins are denatured to probe protein structure (Katta & Chait, 1991aLeBlanc et al, 1991;Loo et al, 1991Loo et al, , 1993b Mirzaet al, 1993). The applicability of mass spectrometry to biological problems would be greatly enhanced and expanded if methodologies were developed to analyze surfactant-containing protein solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was not long after the acceptance of ESI MS as a tool for measuring masses of macromolecular ions that observations were made linking the dramatic changes of ionic charge state distributions to protein denaturation in solution [6,7]. These observations brought about the realization of the potential of ESI MS as a means of probing protein higher order structure and detecting large-scale conformational transitions in solution.…”
mentioning
confidence: 99%
“…One outstanding challenge in ESI mass spectrometry is to accurately predict the observed charge state distribution of a large molecule, given its primary structure, the composition of the solvent system from which the ions are formed, instrumental conditions, etc. Several factors have been shown to influence the observed charge state distribution, including molecular conformation [4][5][6], acid-base chemistry both in solution and in the gas phase [7][8][9][10][11], solvent composition [8], instrumental factors, etc. Several models have been proposed to qualitatively account for some of these effects [12][13][14][15].…”
mentioning
confidence: 99%
“…Loo et al [6] found that charge state distributions correlate with the denaturing capacities of different solvents.…”
mentioning
confidence: 99%